2015
DOI: 10.1177/1756287215581556
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of nitrofurantoin in outpatient male veterans

Abstract: Objectives: The aim of the study was to assess both the safety and the effectiveness of nitrofurantoin in male veterans treated for urinary tract infections (UTIs) with varying degrees of renal impairment in the outpatient setting. Nitrofurantoin is an important oral option for treating UTIs given increasing resistance to commonly used agents. Nitrofurantoin is currently contraindicated in patients with a creatinine clearance (CrCl) of < 60 ml/min, but the reason for this threshold has not been well documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
17
0
2
Order By: Relevance
“…However, nitrofurantoin achieves poor levels in tissue and serum and thus is only appropriate in patients who have cystitis without suspicion for upper tract disease. A retrospective study of male veterans with UTI treated with nitrofurantoin showed a clinical cure rate of 77% rate, which is comparable to other agents [71]. Decreased creatinine clearance predicted clinical failure in this study; however, two additional studies in older adults, one limited to women, refuted the concern that nitrofurantoin is less effective in treating UTI in patients with reduced creatinine clearance [7273].…”
Section: Treatment Of Utismentioning
confidence: 64%
“…However, nitrofurantoin achieves poor levels in tissue and serum and thus is only appropriate in patients who have cystitis without suspicion for upper tract disease. A retrospective study of male veterans with UTI treated with nitrofurantoin showed a clinical cure rate of 77% rate, which is comparable to other agents [71]. Decreased creatinine clearance predicted clinical failure in this study; however, two additional studies in older adults, one limited to women, refuted the concern that nitrofurantoin is less effective in treating UTI in patients with reduced creatinine clearance [7273].…”
Section: Treatment Of Utismentioning
confidence: 64%
“…Nitrofurantoin is especially used to treat UTIs caused by Gram-negative bacteria, particularly Escherichia coli. 22 Nitrofurantoin is being advised for adults and children in the therapy of acute symptomatic UTIs. Also, prescribed for the treatment of recurrent UTIs and for the prophylaxis of recurrent UTIs.…”
Section: Discussion Therapeutic Uses Of Nitrofurantoinmentioning
confidence: 99%
“…Nitrofurantoin is bactericidal in nature, nonspecific molecular target, and limited exposure beyond urinary tract may have the advantage with low resistance rate seen with this antibiotic. 22 Nitrofurantoin has remained successful after many decades of extensive use worldwide with very low resistance rate. 76 Nitrofurantoin ESBL production (24%)…”
Section: Acute Reactionmentioning
confidence: 99%
“…However, there are ongoing discussions regarding the safety and efficacy of treating acute cystitis in male patients as uncomplicated UTIs [13]. Some newer studies suggest that men with acute cystitis do not need treatment for more than 5-7 days [14][15][16], and others argue that nitrofurantoin or pivmecillinam are appropriate as empirical treatment options [17,18].…”
Section: Introductionmentioning
confidence: 99%